1993
DOI: 10.1111/j.1476-5381.1993.tb13820.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cholecystokinin receptor types in pathways controlling oxytocin secretion

Abstract: 1 Intravenous administration of cholecystokinin (CCK) results in a transient activation of oxytocin neurones in the rat, and hence to oxytocin secretion: this activation is followed by expression of c-fos mRNA and of Fos-like immunoreactivity (Fos-LI) in magnocellular oxytocin neurones. Fos-like immunoreactivity is also induced in the regions of the brainstem that are thought to relay information from the periphery to the hypothalamus. 2 Administration of the selective CCKA receptor antagonist MK-329, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 37 publications
(35 reference statements)
2
27
1
1
Order By: Relevance
“…There is evidence to support HPA activation by CCK via peripheral pathways (Kamilaris et al 1992), but direct effects via central or pituitary CCK receptors have also been implicated (Kamilaris et al 1992;Millington et al 1992;Reisine and Jensen 1986). Both the CCK-A receptor (Luckman et al 1993;Millington et al 1992) and a novel (non-A, non-B) receptor subtype may be involved (Parrott and Forsling 1992;Reisine and Jensen 1986), although the human work has shown highly selective CCK-B agonists to be potent ACTH secretagogues de Montigny 1989;Koszycki et al 1996). Both corticotropin-releasing hormone (CRH) (Biró et al 1993;Kamilaris et al 1992) and AVP (Bondy et al 1989;DeBold et al 1984;Mezey et al 1986;Verbalis et al 1987) have also been implicated as mediators in animal work.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to support HPA activation by CCK via peripheral pathways (Kamilaris et al 1992), but direct effects via central or pituitary CCK receptors have also been implicated (Kamilaris et al 1992;Millington et al 1992;Reisine and Jensen 1986). Both the CCK-A receptor (Luckman et al 1993;Millington et al 1992) and a novel (non-A, non-B) receptor subtype may be involved (Parrott and Forsling 1992;Reisine and Jensen 1986), although the human work has shown highly selective CCK-B agonists to be potent ACTH secretagogues de Montigny 1989;Koszycki et al 1996). Both corticotropin-releasing hormone (CRH) (Biró et al 1993;Kamilaris et al 1992) and AVP (Bondy et al 1989;DeBold et al 1984;Mezey et al 1986;Verbalis et al 1987) have also been implicated as mediators in animal work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the chemosensitivity of area postrema neurons to several kinds of intestine peptide hormones that contribute to the feeding regulation, including CCK, which is known as a hunger suppressant (Carpenter et al, 1983;Funahashi and Adachi, 1993;Sun and Ferguson, 1997). It has been shown that systemic infusion of CCK induced cFos expression in the area postrema, indicates that it is a receptive site for circulating CCK (Luckman et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Intravenous administration of CCK results in a tran sient activation of c-fos in oxytocin neurons [33,34], and these activated oxytocin neurons project to the dorsal vagal complex [35], Our results show that some CCKB receptormRNA-expressing neurons observed after salt loading are located in the most dorsal and ventral parts of the PVN. These regions are known to project to the lower brainstem and spinal cord [36][37][38], Salt loading may thus induce increased CCKB receptor mRNA in neurons projecting to the lower brainstem and spinal cord and an increase in the availability of CCK receptors at these sites.…”
Section: Discussionmentioning
confidence: 59%